Probabilistic analysis of time reduction by eliminating barriers in parallel programmes. (6th June 2011) - Yonezawa, Naoki; Kino, Issei; Wada, Koichi
Since barrier synchronisation is a simple means to guarantee the order of data producing and data consuming, it is often used in parallel programmes. However, barrier synchronisation causes the processors' idle time to increase. To reduce the overhead of barrier synchronisation, we have proposed an algorithm which eliminates barrier synchronisations and evaluated its validity experimentally. In this paper, we model the behaviour of parallel programmes and stochastically analyse our algorithm. Using the behavioural model, we evaluated the execution time before eliminating barrier synchronisations as well as after eliminating barrier synchronisations. As a result, we confirmed the observations, which we have found experimentally, that is: 1) the ratio of improvement increases as the number of processors increases: 2) the balance of the load affects the improvement which is gained from eliminating barriers.